Suppression of transient enhanced diffusion in sub-micron patterned silicon template by dislocation loops formation - Kuan-Kan Hu; Ruey-Dar Chang; Wei Yen Woon (AIP Advances, 2015)
We investigate the evolution of two dimensional transient enhanced diffusion (TED) of phosphorus in sub-micron scale patterned silicon template. Samples doped with low dose phosphorus with and without high dose silicon self-implantation, were annealed for various durations. Dopant diffusion is probed with plane-view scanning capacitance microscopy. The measurement revealed two phases of TED. Significant suppression in the second phase TED is observed for samples with high dose self-implantation. Transmission electron microscopy suggests the suppressed TED is related to the evolution of end of range defect formed around ion implantation sidewalls.